Sistem Pelaksanaan Pembelajaran Pendidikan Agama Hindu Pada Masa Pandemi Covid-19 Di SMAN Kuala Kapuas Kabupaten Kapuas - Wati Wati; Pranata Pranata; I Nyoman Sidi Astawa (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
The learning system during the Covid-19 pandemic experienced many changes in the implementation of learning which became a problem in the world of education in schools, including high schools. The issue of education during the Covid-19 pandemic has become the focus of various studies. However, the system for implementing learning, especially Hindu religious education in high schools in Kapuas district, is not yet available. Thus, researchers are interested in studying the learning implementation system at SMA Negeri Kuala Kapuas with the focus on problems (1) How is the readiness to implement the implementation system of Hindu religious education during the Covid-19 pandemic at SMAN Kuala Kapuas, Kapuas Regency, (2) How is the system applied in implementation of Hindu religious education learning during the Covid-19 period at SMAN Kuala Kapuas, Kapuas Regency, and (3) What were the obstacles and solutions faced in the implementation of Hindu religious education learning systems during the Covid-19 pandemic at SMAN Kuala Kapuas, Kapuas Regency. The theory used to study and describe the formulation of the research problem is the theory of behaviorism, systems theory, and cognitive theory. The research method used is a qualitative research method. Data obtained from observations, in-depth interviews, and document studies. The results of the analysis of the learning implementation system show the following points. (1) readiness for the implementation of online learning, namely the readiness of teachers, students and supporting infrastructure for online learning, while limited PTM is the readiness of schedules and health protocols. (2) The system applied in the implementation of learning is full online learning, learning with assignments, and limited PTM with the application of health protocols. (3) The obstacles faced by schools are the knowledge of teachers and students regarding online learning is still diverse, lessons are difficult for students to understand in online learning, and the availability of facilities and infrastructure is not adequate. The solutions offered in the learning implementation system during the pandemic are increasing the creativity of teachers and students and implementing limited face-to-face learning to meet the needs of students in learning.